UPAYA MENGEMBANGKAN KECERDASAN KINESTETIK PADA ANAK USIA DINI MELALUI METODE PERMAINAN TRADISIONAL SUNDA MANDA : DEVELOPING KINESTHETIC INTELLIGENCE IN EARLY CHILDHOOD THROUGH THE TRADITIONAL SUNDA MANDA GAME - Wardoyo, Anwardiani Iftaqul Janah; Ngaisah, Nur Cahyati (Thufuli, 2023)
Kinesthetic intelligence is an important part of the child's motor development process through coordinated movement activities and can train children in skills, balance, strength, flexibility and agility. The low level of kinesthetic intelligence is influenced by several factors such as motion activity that is not optimal, so it requires activities that attract children to activities such as playing Sundanese which creates a variety of movements for those who play it. The method used in this study was qualitative with five children aged 5-7 years as the research subjects. The research was conducted in the Klurak Baru area, Bokoharjo, Prambanan, Sleman using observation instruments and interviews conducted with parents or the surrounding community. The analysis technique uses data condensation, presenting the results and making conclusions. The validity of the data was carried out using a training technique. The findings in this study are that kinesthetic intelligence in traditional Sundanese games can train complex coordination movements such as leg strength when jumping on one leg along with throwing and catching gaco using the hands while moving around. Besides that, it can also train children's balance, limb strength, child agility and child agility in moving activities. Therefore it can be concluded that kinesthetic intelligence can be developed through the traditional Sundanese game method.